The consequence of Antarctic meltwater input on the Atlantic meridional overturning circulation: A non-monotonic response ... - Shin, Yechul; Kug, Jong-Seong; Noh, Kyung Min (GFZ German Research Centre for Geosciences, 2023)
<!--!introduction!--> The Atlantic meridional overturning circulation (AMOC) is crucial in regulating the global climate, and understanding its potential changes under climate change is important. There is growing concern about the impact of natural processes, such as Antarctic meltwater discharge, that are not accounted for in current climate models on a global scale. In this study, we hence carried out idealized experiments to investigate the AMOC's response to Antarctic meltwater input, finding a non-monotonic response of AMOC. The meltwater-instigated cold SST propagates globally, ultimately strengthening the AMOC through enhanced convection in the subpolar northern Atlantic. However, in the early stages, a tropical SST pattern excites an atmospheric teleconnection, weakening the convection, and resulting in even weaker AMOC. This non-monotonic impact highlights the importance of the atmosphere in pole-to-pole interactions and raises the possibility of abrupt climate change in the future. ... : The 28th IUGG General Assembly (IUGG2023) (Berlin 2023) ...